Caliph Al-Mansur and Hulagu Khan - Siddiq, Sayma Aamal; Islam, Arshad (IIUM Press, International Islamic University Malaysia, 2017)
This research discusses life and careers of the Mongol Khan Hulagu and the Abbasid Caliph Mansur in the light of the Machiavellian leadership theory. It aims to explore whether Machiavellianism is a necessary attribute in ensuring an undisputed rule or dominion. Although Machiavelli’s advocacy of ruthlessness and deception promises a successful, unchallenged reign, it largely ignores the psychological aspect as well as the repercussions of suppressing the spiritual self. With reference to al-Mansur, who epitomized the Machiavellian prince, it can be deduced that this eventually leads to psychological trauma, as a result of guilt and fear of retribution, casting a shadow on one’s political success.